Unity in diverse society of Malaysia - Mansoureh Ebrahimi; Kamaruzaman Yusoff; Asmady Idris (The global goals, 2025)
Objective: This article aims to use historical institutionalism to examine how the Malay Bumiputera Muslims identity was constructed and analyse people’s responses to related government policies. Theoretical Framework: The role of religion in constructing an identity for Malay Bumiputera (son of the soil) Muslims, who form the majority of the population, is a topic of debate among Malaysians. Since independence in 1957, the supreme law of Malaysia, the Federal Constitution, has pronounced Islam as the official religion but other religious ideologies are allowed to be practiced. Apart from the race riots of 1969, Malaysians have been living in a harmonious and peaceful multi-ethnic, multi-cultural and multi-religious society; where each ethnicity promotes its own culture, while also respecting other diversities and cherishing differences to promote unity. This study applies the HI framework to examine the identity construction of Malay Bumiputera Muslims and also assess people’s responses to related government policies. Method: For empirical data analysis, the authors employ qualitative method through historical analysis based on authentic sources available in libraries as well as interviews with key informants in order to collect data from their personal opinion and experience. In other words, this comprehensive study has used mixed methods beginning with documentary analysis and using qualitative interviews to support the documentary analysis to achieve our objectives. Results and Discussion: The government has taken many steps to promote stability and racial harmony. Still, there are hurdles such as economic disparities among ethnicities, education based on vernacular languages, and others. On top of that, there are vast differences in community identity construction between the Malay Peninsula and the Borneo states, Sabah and Sarawak. To some extent, however, this historical setting has shaped Malaysian politics to be primarily centred upon the Malay and Bumiputera racial-hegemony context. This political setting cannot be avoided, but other ethnics are also permitted to form parties to represent their communities. Conclusion: To conclude, this identity construction has been a way to provide unity in diversity in the multi-racial society which is politically and socioeconomically constructed.